PENERAPAN MODEL KOOPERATIF THINK PAIR SHARE DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN FIQIH SISWA KELAS IX MADRASAH TSANAWIYAH LABORATORIUM IKIP AL WASHLIYAH MEDAN TA. 2019/2020 - Afni, Putri Laila (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
Application of Think Pair Share (TPS) Cooperative Learning Models in Fiqh Subjects in Class IX MTs Lab. IKIP Al Washliyah Medan went as expected. Based on the percentage of completeness after each student is implemented pesra students get results with an average value of 82.1% of the teacher's role in fiqh learning in the Think Pair Share Cooperative Learning model (TPS). Before teaching in advance the teacher makes a lesson plan so that the learning process is achieved, explains the instructional objectives, reminds students of learning competencies, provides motivation to students, provides material, presents steps in the TPS model, provides suggestions and conclusions on learning material. Supporting factors: the policy of the principal itself, openness of students, supporting instruments, namely the completeness of school facilities and infrastructure. Inhibiting factors: the diversity and diversity of student characters, the handling will also vary according to the child's condition.